A Comprehensive Analysis of the Effects of Physical Activity, Rehabilitation Methods, Environmental and Behavioral Interventions on the Development and Progression of Myopia - Łabuś, Małgorzata; Krzykawski, Karol; Sadowski, Jakub; Papież, Łukasz Stanisław; Maciejczyk, Tomasz; Dołęga, Julia; Mól, Piotr; Zabawa, Bartłomiej; Hudzińska, Patrycja; Sieńko, Antoni (Quality in Sport, 2025)
Introduction: Myopia has become a significant public health problem. Traditional approaches focused on optical correction, but evidence points to the role of comprehensive intervention strategies. The aim of this review is to assess the effectiveness of physical activity, rehabilitation, and environmental and behavioral interventions in controlling the development and progression of myopia. Materials and Methods: Conducted study involved review of the literature using databases such as PubMed, NCBI, and Google Scholar. In the searching process the terms “myopia”, “physical activity”, “diet” and “rehabilitation” were used. State of knowledge: The global prevalence of myopia increased from 28.3% in 2010 to 34.0% in 2020, with a projected increase to 50% of the world's population by 2050. Risk factors include genetic and environmental predispositions. Outdoor physical activity can reduce the risk of developing myopia by about 40%. Optical interventions, such as MiSight lenses, showed a 59% reduction in the change of uncorrected spherical equivalent. Low-concentration atropine eye drops also showed promising results. Environmental factors can influence the development of myopia. Dietary and supplementary interventions show potential in modulating myopia development, although results are inconclusive. Conclusions: A comprehensive approach combining physical activity, optical and pharmacological interventions, environmental modifications, and health education appears to be a promising strategy in preventing and controlling myopia progression. Further research is needed on the mechanisms of myopia development and optimization of intervention strategies.